Role of Commodity Market in Economic Development: A Study of Major Markets of Bagamati Province - Dhungel, Lila Nath; Mahat, Kushendra Bahadur; Panta, Sushil Kumar (NPRC Journal of Multidisciplinary Research, 2024)
Market usually plays a vigorous role fulfilled peoples demand and also strengthen the capacity of trade management system, always support the national economy of the country. Supply system and demands maintain the requirement and functional operations in a market. This study aims to analysis the role of commodity markets in the positive economic development in context of Nepal. The major markets such as Narayanghat, Nuwakot, and Banepa from the Bagamati Province were chosen representative purposively samples. The study was further executed through the primary and secondary research mode as well as consultative meetings and Key Informant Interview were conducted.The study revealed that Paddy, wheat and maize cereals are the topmost commodities in the area. Paddy is high in demands due to consumption. The local producers sufficient for some 2-3 months during season, for the rest of the months,’ supply from neighbor’s district, Terai region and India playing a leading role to fill the demand, agent booking is another mode of supply, India and Terai region are the major sources of supply management. Some 60 % local production are available for 2-3 months in the local market making income and contributing the national economy. Study concluded, as local production played a vital role in the economy of the nations due to comprehensive farm gate price and ongoing supply. Local production strengthening is advised.